Contextually Based Mathematics Learning Module Improves Students' Mathematical Literacy Abilities - Machfud Fatkurochman; Isnandar Slamet; Ikrar Pramudya (Journal of Education Reseach and Evaluation, 2024)
Literacy skills make a real contribution to social and economic growth and welfare for individuals or society. However, currently, students have low mathematical literacy. This research aims to develop contextual-based mathematics learning modules to improve students' mathematical literacy skills. This type of research is development research, with the development model used as ADDIE. Data collection methods use observation, interviews, questionnaires and tests. Data collection instruments used questionnaire sheets and test questions. Data analysis techniques use descriptive and inferential statistical analysis. The results of the research are that the validity of experts, including material experts, is categorized as good, with an average value of 74.84%. Media experts are 81.11% (very good). Linguist is 84.44% (very good). The practicality of the learning module based on teacher responses after going through the trial was stated to be very practical, with an average score of 87.14%. Practicality based on student responses is 85.11% (very practical). The results of the effectiveness of this learning module in increasing mathematical literacy are included in the effective category. Learning outcomes using this module are better in improving mathematical literacy than without using this module. It was concluded that the learning module developed was valid, practical and effective. This research implies that the module developed is suitable for use and utilized as a learning medium to improve students' mathematical literacy.